Applying PRINCE2 project management disciplines to address key risks in ERP System Implementation Projects - Plotnikova, Svetlana (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MAcc (Accountancy))--University of Stellenbosch, 2007.